Del marco tradicional al escenario urbano: Plantas ancestrales devenidas suplementos dietéticos en la conurbación Buenos Aires-La Plata, Argentina - Hurrell, Julio Alberto (2013)
This paper includes partial results of a research in urban Ethnobotany at the conurbation Buenos Aires-La Plata, Argentina. Five species with medicinal and food traditional uses, which are commercialized as dietary supplements were studied: Annona muricata L. (Annonaceae), Euterpe oleracea Mart. (Arecaceae), Lycium barbarum L. (Solanaceae), Plukenetia volubilis L. (Euphorbiaceae) y Smallanthus sonchifolius (Poepp. & Engl.) H.Rob. (Asteraceae). The analysis of the circulation of these products contributes to the understanding of local botanical knowledge, that includes nontraditional components and others linked to the traditions of two immigrant groups: Bolivian and Chinese. The products recently entered the commercial circuit where they are considered as nutraceuticals and adaptogens. Traditional uses of these plants, their properties claimed in pluricultural urban context as well as the scientifically studied ones were compared. Thus, modifications in the original uses as a result of the expansion of the products in the nontraditional commercial context were evaluated.